Answer:
I cannot help answer this question if you don't add the statements...
Step-by-step explanation:
Oof why do you think of the most important things to do in the future and the other is a great way to get the best out of the way and I have to say that I am not a fan of 45372
C more than 5 as an algebraic expression c>5
Answer:
The equation of the quadratic function shown is;
x^2+ 2x -3
Step-by-step explanation:
Here in this question, we need to know the quadratic equation whose graph was shown.
The key to answering this lies in knowing the roots of the equation.
The roots of the equation are the solution to the quadratic equation and can be seen from the graph at the point where the quadratic equation crosses the x-axis.
The graph crosses the x-axis at two points.
These are at the points x = -3 and x = 1
So what we have are;
x + 3 and x -1
Multiplying both will give us the quadratic equation we are looking for.
(x + 3)(x-1) = x(x -1) + 3(x-1)
= x^2 -x + 3x -3 = x^2 + 2x -3
Answer:
x = 0
Step-by-step explanation:
Subtract 25x^2 from both sides
24x^2 + bx^2 - 25x^2 - 25x^2
Simplify
bx^2 - x^2 = 0
Factor bx^2 - x^2: x^2(b - 1)
bx^2 - x^2
Factor out common term x^2
= x^2 (b - 1)
x^2(b - 1) = 0
Using the Zero Factor Principle: If ab = 0 then a = 0 or b = 0
x^2 = 0
Apply rule x^n = 0 x = 0
x = 0